Influência de três modos de fotoativação sobre a sorção e solubilidade de diferentes resinas compostas - Matumoto, Marçal Seitaro (2015)
The aim of this study was evaluate the influence of three techniques of photoactivation, in the sorption (SO) and solubility (SL) of three composite resins Filtek Z350 XT, Tetric N-Ceram and IPS Empress Direct. It was prepared 90 specimen (CP) of 8mm of diameter and 1mm of thickness and divided in 9 groups (n=10). The CP were photoactivated by a LED Bluephase device following these techniques: Convencional (CONV); Soft-Start (SS) and Pulse Delay (PA). They were then placed in a desiccator containing silica gel at 37°C and weighed daily until obtainment of a constant mass m1. Then, they were immerse in deionized water for seven days and weighed (m2). The reconditioning of the CP were accomplished following the procedure of m1 until the obtainment of a constant mass (m3). The values of SO and SL was calculated according to ISO 4049 and submitted to the ANOVA test (two-way) followed by the pos hoc of Turkey, p<0.05. There were no significant statistical differences in SO and SL when compared to the photoactivation techniques for all tested resins. In the analysis of SL, no significant statistical differences between the materials and the photoactivation techniques were observed. As for the composite resin Filtek Z350 XT, statistically higher results to other resins was evaluated. It was concluded that the different forms of photoactivation did not influence in the SO and SL of the tested composite resins.